High-Quality Schottky Barrier Diodes on β-Gallium Oxide Thin Films on Glass Substrate. (1st January 2019) - Müller, Stefan; Thyen, Laurenz; Splith, Daniel; Reinhardt, Anna; von Wenckstern, Holger; Grundmann, Marius
Abstract : Structural, electrical and optical properties of monoclinic gallium oxide thin films, deposited by pulsed laser deposition on glass substrates, are reported. The influence of growth temperature on thin film properties was investigated. Further, Ga2 O3 buffer layers, grown and/or annealed at different temperatures, can be used to reduce the surface roughness of subsequently grown thin films. On thin films obtained from optimized growth parameters, Schottky barrier diodes were fabricated by reactive magnetron sputtering of Pt. Interestingly, Schottky diodes realized on thin films on glass substrate (without optimized buffer layer) have similarly good properties as diodes realized on thin films grown epitaxially on c -plane sapphire. The results stimulate realization of e. g. solar-blind photo detectors on low cost and possibly large area glass substrates.